The Lingering Effects: Examining mental health in India during a period of COVID-19 regression - Amandeep Dhaliwal (ACHSM, 2022)
Purpose: COVID-19 has been recognized as a contagious disease which can cause serious health problems, even proving to be fatal in some cases. The swift spread of COVID-19 epidemic shook the world which led to lockdowns, isolation, and social distancing for the general population so as to curb and contain the spread. This was found to lead to mental health disorders amongst people. This study examines the prevalence and severity of anxiety, stress perception, and well-being levels among the people at the time when the COVID-19 was in regression (decline) in India. Methods: In this cross-sectional study, 374 respondents' mental health was evaluated using three standardized questionnaires: Generalized Anxiety Disorder [GAD-7], Perceived Stress Scale [PSS-4], and Five Wellbeing Index [WHO-5]. Results: The study revealed that almost 82% of respondents had moderate to severe levels of stress while 66% of respondents had mild to moderate levels of anxiety. Overall, 60% of respondents had poor (low) mental well-being. A strong negative correlation was found between mental well-being and perceived stress, and mental well-being and level of anxiety, in comparison to the correlation between anxiety and perceived stress was positive and statistically significant. Conclusions: This study identified several long-term psychological effects of COVID. The presence of stress and anxiety and poorer mental well-being even at the time of decline in COVID-19 cases, highlights the need for serious attention to be given to psychological and psychiatric help and support throughout the duration and regression of such diseases. Health policymakers must ensure coherent and consistent plans for screening the mental health of the general population are in place to provide the required support in managing the long-term psychological and psychiatric effects of COVID.